Enchanced expression of hexokinase I in pancreatic islets induced by sucrose administration - Maiztegui, Bárbara (2006)
Administration of a sucrose-rich diet (SRD) to normal amsters induces an insulin-resistant state and a significant increase of insulin secretion and β-cell mass. Islets isolated from these animals had a marked increase in glucose metabolism and glucose-induced insulin secretion, at both low and high glucose concentrations. They also presented increased hexokinase (HK) activity, without measurable changes in glucokinase (GK) activity. In this study we measured HK and GK activity in homogenates of islets isolated from normal control and SRD-fed hamsters, as well as in their particulate and cytosolic fractions. We also measured transcription rate (m-RNA by reverse transcriptase PCR) and expression levels (Western blotting) of both enzymes in these islets. We found an increase in HK activity and expression levels, without measurable changes in HK mRNA level in SRD-fed animals. Whereas a similar GK activity was measured in homogenates of islets isolated from both groups, such activity was significantly higher in the cytosolic fraction of SRD islets. On the other hand, GK transcription rate and expression level were similar in both experimental groups. Our results suggest that the increased β-cell secretory response to low glucose can be partly ascribed to an increased activity of islet HK consecutive to an enhanced expression of the enzyme, while the enhanced response to high glucose could be due to changes in GK compartmentalization.